Had We But Worlds Enough, and Time, This Absolute, Philosopher... - Clemens, Justin (Cosmos and History: The Journal of Natural and Social Philosophy, 2006)
In Logiques des Mondes, Paris, Seuil, 2006, Alain Badiou has produced a sequel to his magnum opus Being and Event. Whereas Being and Event primarily restricted itself to the relationship between ontology and the event, mathematics and poetry, the new book seriously extends and revises certain of its predecessor#39;s propositions in order to construct a logic of different ’worlds’; This article outlines some of the major doctrines, arguments, and motivations for the new work, as well as several points of possible difficulty.